Non-comparative and comparative advertising in oligopolistic markets - Maria Alipranti; Evangelos Mitrokostas; Emmanuel Petrakis (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
We study firms' advertising strategies in an oligopolistic market in which both non-comparative and comparative advertising are present. We show that in equilibrium firms mix over the two types of advertising, with the intensity of comparative advertising exceeding that of non-comparative advertising; moreover, that the intensity of comparative increases relatively to non-comparative advertising as market competition intensifies. Interestingly, the use of comparative advertising may lead to higher consumers' surplus and welfare in a mixed advertising market than in the absence of advertising or when either comparative or non-comparative advertising is not present.
Keywords: L13; M37; 330; Comparative Advertising; Non-comparative advertising; Oligopoly; Product Differentiation